Best bilinear approximations of the classes S^Ω_p, θB of periodic functions of many variables - Solich, K. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We obtain exact-order estimates of the best bilinear approximations of classes S^Ω_p, θB of periodic functions of many variables in the space L_q for some relations between parameters p, q, θ.